2012
DOI: 10.3758/s13428-012-0243-8
|View full text |Cite
|
Sign up to set email alerts
|

Norms of valence, arousal, dominance, and age of acquisition for 4,300 Dutch words

Abstract: This article presents norms of valence/pleasantness, activity/arousal, power/dominance, and age of acquisition for 4,300 Dutch words, mainly nouns, adjectives, adverbs, and verbs. The norms are based on ratings with a 7-point Likert scale by independent groups of students from two Belgian (Ghent and Leuven) and two Dutch (Rotterdam and Leiden-Amsterdam) samples. For each variable, we obtained high split-half reliabilities within each sample and high correlations between samples. In addition, the valence rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
330
8
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 267 publications
(370 citation statements)
references
References 52 publications
27
330
8
5
Order By: Relevance
“…Ghent and Leuven are two towns in Flanders (the Dutch speaking half of Belgium) separated by 80 km. Moors et al (2013) found no differences in the ratings of the two universities for the variables they investigated, and there are no reasons to expect this would be otherwise for the present ratings. Still, as a precaution, the Ghent students provided the AoA norms, given that all previous AoA ratings in Dutch were collected there.…”
Section: Participantsmentioning
confidence: 60%
See 4 more Smart Citations
“…Ghent and Leuven are two towns in Flanders (the Dutch speaking half of Belgium) separated by 80 km. Moors et al (2013) found no differences in the ratings of the two universities for the variables they investigated, and there are no reasons to expect this would be otherwise for the present ratings. Still, as a precaution, the Ghent students provided the AoA norms, given that all previous AoA ratings in Dutch were collected there.…”
Section: Participantsmentioning
confidence: 60%
“…The importance of familiarity is likely to be minimal, once one has a good word frequency measure and information about AoA (Brysbaert & Cortese, 2011). Valence and arousal have recently gained interest (e.g., Kuperman et al, in press) but could not be included in the present study (see, however, Moors et al, 2013, who collected values for 4,300 words).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations